Assessment of Knowledge, Attitude, Handwashing Practices and its associated factors Among Mothers of Children Presenting in Paediatric Department of a Tertiary Care Hospital of a Developing Country. - Maqbool, Shahzaib; Haider, Maryam; Iqbal, Ather; Ihtesham, Arham; Mohamed, Waleed Inayat; Langove, Muhammad Nadeem; Arsh, Laraib; Sundus, Omaima; Haider, Syed Turab; Omer, Hassam (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Despite remarkable progress in scientific methods and measures against infectious disease transmission, the prevalence of infectious diseases is still on the rise in resource-poor countries. Hand hygiene is considered an effective way of fighting against deadly infectious diseases. Our study aimed to assess knowledge, attitude, and hand hygiene practices among mothers of children presenting for routine paediatric check-up in the department of paediatrics in a tertiary care hospital of Rawalpindi. Materials and Methods: It’s a descriptive cross-sectional study involving 400 mothers from the paediatric department of the Holy family hospital (HFH), Rawalpindi. A convenient sampling technique was used to select the study participants. A semi-structured, pre-tested questionnaire that included demographic details, knowledge, attitude, and practice levels were assessed through validated questionnaires used in previously published studies. Descriptive statistics were used for demographic details and chi-square analysis was used to find an association between handwashing practice with knowledge and attitude. A P<0.05 was taken as significant. Data analysis was done through SPSS.v.23. Results and Discussion: In total, 400 females participated in the study and the mean age (±SD) was 32.4±10.2 years. The mean age of children was 31.2±12.2 months. The level of good handwashing knowledge and attitude was 93% and 60% respectively. However, the level of good handwashing practice was just 40%. The age of mothers, residential area, occupation, socioeconomic status, and the level of knowledge regarding handwashing, showed significant association with handwashing practices. Conclusion: In our study handwashing practice among mothers was relatively low. Age of mothers, residential area, occupation, socioeconomic status, and the level of knowledge regarding handwashing, were significantly associated with handwashing practices. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 418-423